Negritude e sofrimento psíquico - Reis Filho, José Tiago dos (2005)
The question of black people in Brazil, is discussed here as a social and individual symptom which brings psychic suffering to black individuals. This discussion is based on the premises of fundamental psychopathology as a proposition of interpretation of the psychic crisis which occur in face of an excess and on the concept of the citizen analyst, that is to say, of this psychoanalyst who inserts himself in society and acts through his speech, which points out fictions to be dismantled and enables individuals to get rid of fixations. The concept of the psychic slave, articulated with the one of the social slave, is very important when we consider the signs of slavery, which are present in our society and in black individuals who suffer from their negritude. Having a past of slavery, this country still lives, in everyday life, situations of prejudice, discrimination and racism, which are clearly expressed in the material conditions of most black people, but also in experiences which are often marked by subjugation to standards of aesthetics and behavior remaining as a narcissistic wound. This study deals with the possibility of healing this wound and walking through this ghost from the point of view of psychoanalysis